UBV-IR photometry and optical spectroscopy of the galactic OB association Bochum 7 - Corti, Mariela (2008)
The lack of tightly bound and easily identifiable young open clusters leads to the quest for OB associations as tracers of spiral arms. Massive stars are usually found in groups, and the presence of a WolfRayet star, WR12 in the catalogue of galactic WR stars (van der Hucht 2001), at α=8h44m47.2s , δ=−45◦58’55.5” (J2000.0), triggered the search for an surrounding OB association, now known as Bochum7 (Moffat & Vogt 1975).